Mixed apocrine/endocrine ductal carcinoma in situ of the breast coexistent with lobular carcinoma in situ. Issue 1 (1st January 2001) - Coyne, J D; Dervan, P A; Barr, L; Baildam, A D
Abstract : An unusual mixed form of ductal carcinoma in situ (DCIS) of the breast is described, which exhibits a biphenotypic morphology encompassing a range of differential diagnostic DCIS subtypes. In adddition, immunophenotypic and ultrastructural studies demonstrate neuroendocrine and apocrine differentiation, raising questions regarding appropriate classification and biological behaviour. In two cases, coexistence of this mixed form of DCIS with lobular carcinoma in situ (LCIS) in the same duct lobular units is an additional unusual feature that might, at least in some cases, indicate a closer relation between them.